When a Red–NIR-Emissive Cs2[Mo6Br14] Interacts with an Active Diureasil–PEO Matrix: Design of Tunable and White-Light-Emitting Hybrid Material - Ferreira Molina, Eduardo; Martins de Jesus, Natana Aparecida; Paofai, Serge; Hammer, Peter [UNESP]; Amela-Cortes, Maria; Robin, Malo; Cordier, Stephane; Molard, Yann (Wiley, 2019)
Hybrid materials that combine diureasil matrices and octahedral molybdenum clusters have been synthesized to design lead-, cadmium- and rare-earth-free emitters for lighting or optoelectronic applications. This association leads to homogeneous and stable hybrids, for which the emission color can be tailored in the entire visible range, including white light; this is thanks to effective energy transfers from the host to the nanocluster.
Keywords: energy transfers; hybrid materials; luminescence; metal clusters